Utility of π and σ-Acceptor Reagents for the Spectrophotometric Determination of Cefotaxime Sodium Antibacterial Drug via Charge Transfer Complex Formation. Issue 4 (2011) - Frag, Eman Y.; Mohamed, Gehad G.; Farag, A.B.; Yussof, E.B.
No abstract available